Tightening the Purse Strings: The Effect of Stricter DI Eligibility Criteria on Labor Supply - Stefan Staubli (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2009)
This paper explores the labor supply effects of a large-scale policy change in the Austrian disability insurance program, which tightened eligibility criteria for men above a certain age. Using administrative data on the universe of Austrian private-sector employees, the results of difference-in-difference type regressions suggest a substantial and statistically significant decline in disability enrollment of 5-5.7 percentage points and a modest increase in employment of 1.4 to 2.7 percentage points. On the other hand, the policy change had important spillover effects into the unemployment and sickness insurance program. Specifically, the share of individuals receiving unemployment benefits increased roughly by 3 percentage points and the share receiving sickness insurance benefits by 0.6 percentage points.
Keywords: H53; H55; J21; J64; J68; 330; Disability Insurance; Eligibility Criteria; Labor Supply; Policy Reform